THE EFFECTIVENESS OF DISCOVERY LEARNING IN IMPROVING ENGLISH WRITING SKILL OF EXTROVERTED AND INTROVERTED STUDENTS - Daniar Sofeny (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
This study aimed to describe the effectiveness of discovery learning in improving English writing skill of extroverted and introverted students which is compared with direct instruction as the traditional learning method. In this research, the researcher employed a quantitative research by using experimental factorial design. The population in this research was the eleventh graders of state senior high school Sale in academic year 2013/ 2014 and the samples were 20 students from both classes and categories. The try out was conducted to measure validity and reliability. And the two ways ANOVA was conducted to test the hypotheses, two-way analysis of variance with F-test at the 5% (0.05) level of significance. The result of this study revealed that the use of discovery learning was effective to the extroverted students than the introverted students. In line with it, the finding indicates that the use of direct instruction was also effective to introverted students than the extroverted students. In other words, the result of the used of discovery learning had a bigger influence to the extroverted students rather than introverted students. Keywords: Discovery Learning; Extroverted; Introverted; Writing Skill.